The end of ethics and a way back : how to fix a fundamentally broken global financial system - Malloch, Theodore Roosevelt; Mamorsky, Jordan D. (New York : Wiley, 2013)
Bestselling author and professor Ted Malloch calls for real financial reform to restore confidence and fairness to a broken system From Ponzi schemes to the credit crisis to the real estate bubble, the financial industry seems to have lost its way on the road to riches. As private greed continues to undermine the public good, one might wonder what ever happened to business ethics. And how can we reform the global financial system to benefit everyone, rather than just the very lucky few? In The End of Ethics and the Way Back, the bestselling author of Doing Virtuous Bu.